Technological catching-up, sales dynamics and employment growth - Dosi, Giovanni,Yu, Xiaodan (Global Labor Organization (GLO), 2018)
This paper investigates the microeconomics of employment dynamics, using a Chinese manufacturing firm-level dataset over the period 1998-2007. It does so in the light of a scheme of
10419/173398
Keywords: Graue Literatur; Employment Growth; Demand; Product Innovation; Process Innovation; Export; China catching-up